Income Diversification and Financial Performance: The Mediating Effect of Banks’ Size, Ownership Structure, and the Financial Crisis in Vietnam - Phan Gia Quyen; Nguyen Tran Thai Ha; Susilo Nur Aji Cokro Darsono; Tran Dang Thanh Minh (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: This study focuses on the correlation between income diversification and financial performance, taking into account banks’ size, type of ownership, and the financial crisis.Design/Methodology/Approach: This study uses financial data of 29 commercial banks in Vietnam during the period from 2005 to 2018. This research employs a Generalized Method of Moments (GMM) regression.Research findings: The results do not find statistical evidence of a direct effect of banks’ income diversification on their financial performance. However, when considering the classification factors, such as the bank’s size and ownership type, the findings show that big banks and state-owned banks could take advantage of diversification strategies to boost their profitability. Moreover, the study has proven that income diversification generates a significant positive effect on banks’ financial performance during the crisis time.Theoretical contribution/Originality: This study provides a theoretical evidence on the direct effect of income diversification on a bank’s financial performance concerning banks’ size, ownership type, and the financial crisis.Practitioner/Policy implication: Further, this research also offers the bank’s managers, policymakers, and investors an insight of good banks’ financial performance in the context of an unstable economy.Research limitation/Implication: The limitations still exist in this research, such as (1) the number of banks participating in the research sample was a predictable limitation; (2) this research mainly focused on financial variables but ignored the variables representing the managers’ behavior and the banks’ organizational structure; (3) the future studies can focus on these aspects to explore further the hidden picture of diversification strategy and banking performance